From traditionalism to new trends: contributions and reflections (Research, Society and Development, 2021)
Today's society yearns for a quality and contextualized education, in which the student has autonomy and can express their ideas. The aim of the article is to understand how Brazilian pedagogical trends can contribute to a significant, innovative and dynamic pedagogical practice, through methods that can be considered active. To achieve this goal, we proposed to observe the existence of active methods in each trend and compare traditional methodologies with new teaching methodologies, thus seeking to identify which contributions both can bring to student learning. Prepared through bibliographical research, documentary and field research, the article seeks to lead teachers, administrators and the entire school community to reflect on the importance of the student's active participation in the learning process, taking into account the historical process of education in Brazil. The research had 14 (fourteen) high school teachers as subjects, working at the Conquista D’Oeste State School. At the end of the research, it is concluded that some teachers do not know the trajectory of Brazilian education, or do not know the definition and characteristics of some pedagogical trends. This leads us to question the structure of the grid and the quality of undergraduate courses and also continuing education, as one of the most present themes in current education is active methodologies.